COVID-19 Experiences in Malaysia - Helmi Salim, Ahmad Munawwar (International Journal of Human and Health Sciences (IJHHS), 2022)
Adapting the whole society approach, IMARET complements the effort by the Ministry of Health in battling the pandemic by working with various parties, which includes United Nation agencies, government agencies, corporate sectors and NGOs. Since 16th March 2020, IMARET has responded to the COVID-19 pandemic by mobilizing medical and non-medical volunteers, and providing medical equipment and supplies to support the healthcare facilities throughout Malaysia. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S11